THREE LANGUAGES FOR THREE CULTURES - Kachanyuk-Spiech, Iryna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
(Works on Literary Studies and Culturology) [1] IRYNA KACHANYUK-SPIECH is an instructor of the Ukrainian language at the Ukrainian Free University in Munich and prolific translator of Ukrainian literature into German. This article was translated and abridged from the author’s «Трьома мовами для трьох культур». Християнський Голос 23.3075 (December 2021) pp. 23-25. [1] Scholarly article reprinted in celebration of the 85th birthday of Prof. Leonid Rudnytzky. Edited Stefan I. Khorob (Ivano-Frankivsk, 2020) 428pp.